A Critical Analysis and Application of Shabdartha Bodhaka Vrutti in Samhita - Chate Vasudev Anandroa; T Niveditha (RGUHS Journal of AYUSH Sciences)
Shabdartha Bodhaka Vrutti provides the insight for finding different shades of meaning for a single word or sentence especially in technical terminologies mentioned in Ayurveda where each word carries diverse meanings shaped by context. This concept unfolds through four aspects Abhidha Laksana Vyanjana and Tatparyakhya Vrutti. Abhidha Vrutti straightforwardly conveys meaning encompassing Roodha Yougika and Yoga Roodha which reveal how words convey meaning through grammar and common usage. Laksana Vrutti implies meanings indirectly with three types Jahallakshana Ajahallakshana and Jahadajahallakshana enriching comprehension beyond literal interpretation. Vyanjana Vutti suggests additional meanings beyond the literal sense posing challenges in understanding direct meanings but offering deeper insights into underlying contexts. Tatparyakhya Vrutti aids in interpreting words with multiple meanings based on context or purpose. This paper discusses these concepts with examples illustrating their significance in Ayurvedic discourse and emphasizing the dynamic nature of languages interaction with context. Understanding lsquoShabdartha Bodhaka Vruttirsquo is crucial for comprehensive knowledge as it uncovers the intricate relationship between words and meanings enriching understanding in medical sciences.